(untitled) (Historia, 2021)
This year, on 11 October, it will be a hundred years since the war between the two Boer republics in South Africa and Great Britain erupted. Quite a few names have been used in the past with reference to this conflict. Today, in planning for the commemoration and with a new attention focused on this war, a sense of controversy surrounds the issue of a 'correct name'. Through the centuries names for wars usually had a spontaneous origin among the people who were involved in a particular conflict. The name often differed from the official name given to the war.